Using Fine Grain Approaches for highly reliable Design of FPGA-based Systems in Space - Niknahad, Mahtab (Steinbuch Series on Advances in Information Technology / Karlsruher Institut für Technologie, Institut für Technik der Informationsverarbeitung, 2013)
Nowadays using SRAM based FPGAs in space missions is increasingly considered due to their flexibility and reprogrammability. A challenge is the devices sensitivity to radiation effects that increased with modern architectures due to smaller CMOS structures. This work proposes fault tolerance methodologies, that are based on a fine grain view to modern reconfigurable architectures. The focus is on SEU mitigation challenges in SRAM based FPGAs which can result in crucial situations.